(untitled) (Eurasian Journal of Ecology, 2016)
This paper is devoted to analysis of Poaceae Barnhart family of Zhetysu Alatau, Analysis has shown that there are 214 species of Poaceae Barnhart family, which are referred to 32 genuses and 16 tribs.